The coupling of bone and cartilage turnover in osteoarthritis: opportunities for bone antiresorptives and anabolics as potential treatments?. Issue 2 (27th November 2013) - Karsdal, M A; Bay-Jensen, A C; Lories, R J; Abramson, S; Spector, T; Pastoureau, P; Christiansen, C; Attur, M; Henriksen, K; Goldring, S R; Kraus, V
Abstract : Osteoarthritis (OA) is the most common form of arthritic disease, and a major cause of disability and impaired quality of life in the elderly. OA is a complex disease of the entire joint, affecting bone, cartilage and synovium that thereby presents multiple targets for treatment. This manuscript will summarise emerging observations from cell biology, preclinical and preliminary clinical trials that elucidate interactions between the bone and cartilage components in particular. Bone and cartilage health are tightly associated. Ample evidence has been found for bone changes during progression of OA including, but not limited to, increased turnover in the subchondral bone, undermineralisation of the trabecular structure, osteophyte formation, bone marrow lesions and sclerosis of the subchondral plate. Meanwhile, a range of investigations has shown positive effects on cartilage health when bone resorption is suppressed, or deterioration of the cartilage when resorption is increased. Known bone therapies, namely oestrogens, selective oestrogen receptor modifiers (SERMs), bisphosphonates, strontium ranelate, calcitonin and parathyroid hormone, might prove useful for treating two critical tissue components of the OA joint, the bone and the cartilage. An optimal treatment for OA likely targets at least these two tissue components. The patient subgroups for whom these therapies are most appropriate have yet to be fully defined but would likely include, at a minimum, those with high bone turnover.